High effusion rates of the Cordón Caulle 2011–2012 eruption (Southern Andes) and their relation with the quasi‐harmonic tremor. Issue 17 (11th September 2015) - Bertin, D.; Lara, L. E.; Basualto, D.; Amigo, Á.; Cardona, C.; Franco, L.; Gil, F.; Lazo, J.
Abstract High effusion rates of intermediate‐to‐high‐silica lavas seem to be less uncommon than previously thought, in particular during their initial eruptive stages. In this study, we report satellite‐based time‐averaged discharge rates for the 2011–2012 effusive phase at Cordón Caulle, which are well correlated with the evolution of the quasi‐harmonic tremor, the most significant seismic signal after the initial explosive stage. Such a correspondence could become a key method for detection of the onset of effusive phases, especially in remote and/or very cloudy areas, supplying an additional tool for effective warnings and near‐real‐time hazard appraisal.